Deletion of calponin 2 attenuates the development of calcific aortic valve disease in ApoE−/− mice. (August 2018) - Plazyo, Olesya; Liu, Rong; Moazzem Hossain, M.; Jin, J.-P.
Abstract: Calcific aortic valve disease (CAVD) is a leading cause of cardiovascular mortality and lacks non-surgical treatment. The pathogenesis of CAVD involves perturbation of valvular cells by mechanical stimuli, including shear stress, pressure load and leaflet stretch, of which the molecular mechanism requires further elucidation. We recently demonstrated that knockout (KO) of Cnn2 gene that encodes calponin isoform 2, a mechanoregulated cytoskeleton protein, attenuates atherosclerosis in Apo E KO mice. Here we report that Cnn2 KO also decreased calcification of the aortic valve in Apo E KO mice, an established model of CAVD. Although myeloid cell-specific Cnn2 KO highly effectively attenuated vascular atherosclerosis that shares many pathogenic processes with CAVD, it did not reduce aortic valve calcification in Apo E KO mice. Indicating a function in the pathogenesis of CAVD, calponin 2 participates in myofibroblast differentiation that is a leading step in the development of CAVD. The aortic valves of Apo E KO mice exhibited increased expression of calponin 2 and smooth muscle actin (SMA), a hallmark of myofibroblasts. The expression of calponin 2 increased during myofibroblast-like differentiation of primary sheep aortic valve interstitial cells and during the osteogenic differentiation of mouse myofibroblasts. Cnn2 KO attenuated TGFβ1-induced differentiation of myofibroblasts in culture as shown by the lower expression of SMA and less calcification than that of wild type (WT) cells. These findings present calponin 2 as a novel molecular target for the treatment and prevention of CAVD. Abstract : Graphic abstract Highlights: CAVD is a leading cause of mortality and lacks non-surgical treatment. Pathogenesis of CAVD involves perturbation of valvular cells by mechanical stimuli. Cnn2 KO attenuates the development of CAVD in Apo E KO mice. Cnn2 KO attenuated TGFβ1-induced differentiation of myofibroblasts. Calponin 2 is a potential molecular target for the treatment and prevention of CAVD.